Interactive Game Using Kinect Sensor - Madhoun, Shahd; Tahboub, Madeha (جامعة بوليتكنك فلسطين - علم حاسوب, 2022)
In recent years, technology has taken over our lives. Everything we do is reliant on technology, particularly in the aftermath of the corona outbreak last year. As a result, technology has a huge impact on all members of society, particularly children. So, this game attempts to increase children's movement while playing video games. One of the most important characteristics of the game is that it relies on the child's movement, maintains a safe distance between the player and the screen so that his vision is not harmed and exposed to issues such as obesity, isolation, and others. The game revolves around a character who must jump, move left and right to avoid obstacles. At the same time the player must collect coins. What is special about this game is that it allows children to be the controller and feel as if they are actually in the game.
Hero Kinect
no of pages 52, علم حاسوب 2/2022
Keywords: Kinect Sensor - games